PJMHS 2023
DOI: 10.53350/pjmhs202317213
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Laryngoscopy Audit in Outpatient Department of a tertiary care hospital, Islamabad

Abstract: Background: Flexible laryngoscopy is less operator/patient dependent diagnostic procedure with magnified field and well tolerated diagnostic procedure. Flexible laryngoscopy is tolerable diagnostic procedure with clear and magnified visualization of interior larynx. Aim: To audit the flexible laryngoscope in outpatient department in our local setting. Methods: A retrospective audit survey was carried out in Outpatient ENT Department of Akbar Niazi Teaching Hospital, Islamabad between June 2021 and May 2022. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Evidence from one study in Malaysia reported depression ranging from 22% to 50% among breast cancer patients (Ram et al, 2013). This finding is comparable to that of research among patients with cancer conducted in Ethiopia (58.4%; Berihun et al, 2017) and in Pakistan (61.6%; Dogar et al, 2009). According to Niedzwiedz et al (2019), depression had a mean prevalence of approximately 13% globally among cancer patients and ranged between 4% to 49% when all evaluation techniques are included.…”
Section: Discussionsupporting
confidence: 84%
“…Evidence from one study in Malaysia reported depression ranging from 22% to 50% among breast cancer patients (Ram et al, 2013). This finding is comparable to that of research among patients with cancer conducted in Ethiopia (58.4%; Berihun et al, 2017) and in Pakistan (61.6%; Dogar et al, 2009). According to Niedzwiedz et al (2019), depression had a mean prevalence of approximately 13% globally among cancer patients and ranged between 4% to 49% when all evaluation techniques are included.…”
Section: Discussionsupporting
confidence: 84%